Understanding administrative law in the common law world - Daly, Paul, 1983- (Oxford : Oxford University Press, 2021)
A new framework for understanding contemporary administrative law, through a comparative analysis of case law from Australia, Canada, England, Ireland, and New Zealand. The author argues that the field is structured by four values: individual self-realisation, good administration, electoral legitimacy and decisional autonomy.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 27, 2021).
Keywords: Administrative law; Administrative law -- Case studies